Digital Mindset And Student Resilience: A Post-Pandemic Study On Learning Motivation In Indonesian High Schools - Solekhah, Devi Zakiyatus; Sakdiyah, Faridatus; Silvia, Fera (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The COVID-19 pandemic has had a profound impact on the education system, forcing schools across Indonesia to rapidly transition to digital learning models. This abrupt shift demanded not only technical mastery of digital tools from students but also psychological readiness to adapt to a new, uncertain learning environment. These challenges raise a critical question: to what extent does students’ digital mindset influence their ability to maintain resilience and sustain learning motivation amidst the pressures and complexities of digital education? This study aims to examine the influence of digital mindset on the resilience and learning motivation of Indonesian secondary school students during the post-pandemic period. A quantitative approach was employed, using a cross-sectional survey design. Data were collected from 110 students through a validated online questionnaire based on a Likert scale, measuring levels of digital mindset, psychological resilience, and learning motivation. The data were analyzed using multiple linear regression to assess the relationships between variables. The results reveal that a digital mindset has a positive and significant effect on both student resilience (β = 0.421; p < 0.01) and learning motivation (β = 0.389; p < 0.01). These findings suggest that students with a higher digital mindset tend to be more adaptive in facing academic challenges and exhibit stronger motivation in digital learning contexts. This study underscores the importance of not only equipping students with digital infrastructure and skills but also fostering their mental capacity to endure and thrive amid ongoing educational transformation. Therefore, strengthening a digital mindset emerges as a key element in cultivating a generation of learners who are resilient, intrinsically motivated, and well-prepared to navigate the future landscape of education.